IBM FlashSystem 5000 and 5200 for Mid-Market - Fonseca, Aldo Araujo (IBM Redbooks, 2021)
The IBM® FlashSystem 5015, 5035, and 5200 help you meet the challenges of rapid data growth while staying within limited IT budgets. These systems allow you to quickly consolidate, simplify, and optimize your IT infrastructure with an efficient, highly flexible, yet easy-to-use storage system with powerful virtualization features. This IBM Redpaper™ publication is intended for mid-market clients.